Correlations among age, sex, axial length, and subfoveal choroidal thickness in the choriocapillaris structure analyzed using multiple en face image averaging optical coherence tomography angiography - Ichioka, Ai; Ooto, Sotaro; Uji, Akihito; Manabe, Saki; Shiragami, Chieko; Tsujikawa, Akitaka (PloS one, 2021)
To analyze the structure of the choriocapillaris in healthy eyes by using averaged en face images acquired using swept source optical coherence tomography angiography and to examine the changes in the macular profile in relation to age, sex, axial length, and choroidal thickness. This prospective, cross-sectional study included 81 eyes of 81 subjects without ophthalmologic or systemic diseases who underwent a full ophthalmologic examination, including 3 × 3-mm macular optical coherence tomography angiography. Four to nine choriocapillaris en face images were registered and averaged. The averaged images were then binarized and analyzed. The averaged choriocapillaris images showed a continuous capillary meshwork, whereas the unaveraged images had a granular appearance. The mean total area and size of flow voids were 0.99 ± 0.20 mm2 and 567.8 ± 201.5 μm2, respectively, and these values correlated positively with age (p = 0.002, R = 0.336 and p = 0.026, R = 0.247, respectively). Age-related gains in the mean total area and flow void size were 4.20 × 10-3 mm2 and 3.07 μm2 per year, respectively. However, the mean total area and flow void size had no significant correlation with axial length, subfoveal choroidal thickness, or sex. Multiple averaged en face swept source optical coherence tomography angiography is more effective than a single optical coherence tomography angiography scan for better visualizing the choriocapillaris. The total area and size of flow voids within a 3 × 3-mm macular area positively correlated with age. This technique can be useful for investigating the changes arising in macular diseases.